2019
DOI: 10.1021/acs.jpcc.9b02876
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Fourier Transform Near- and Mid-Infrared Spectroscopy for Measurement of Energy Levels of Electron Trapping Sites in Titanium(IV) Oxide Photocatalyst Powders

Abstract: Electron trapping sites in titanium(IV) oxide photocatalyst powders were investigated by photoacoustic (PA) Fourier transform near-infrared spectroscopy (FT-NIR) and mid-infrared spectroscopy (FT-MIR). PA measurements using FT-NIR and FT-MIR enabled in situ observation of the energy levels of electron trapping sites in wide energy levels (0.1−1.9 eV) below the bottom of the conduction band. During ultraviolet (UV) irradiation, PA intensity increased depending on the wavenumber, and changes in the PA spectra we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 50 publications
3
33
0
Order By: Relevance
“…A close resemblance in the electron paramagnetic resonance spectrum between anatase and brookite was noticed by Livraghi et al , indicating a similar electron trapping behavior between them . A defect level was detected to lie 1.1 eV below the CBM of brookite by Shinoda and Murakami . Additionally, Vequizo et al found a moderate depth of 0.4 eV below the CBM for the trapped electron in brookite .…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…A close resemblance in the electron paramagnetic resonance spectrum between anatase and brookite was noticed by Livraghi et al , indicating a similar electron trapping behavior between them . A defect level was detected to lie 1.1 eV below the CBM of brookite by Shinoda and Murakami . Additionally, Vequizo et al found a moderate depth of 0.4 eV below the CBM for the trapped electron in brookite .…”
Section: Introductionsupporting
confidence: 55%
“…Experiments have detected two defect bands in brookite which are 0.4 and 1.1 eV below the CBM. 67,68 From our GW calculations, it seems that polaronic states of Ov near the surface may all together contribute to the shallow defect band, while the deep defect band may result from the ddσ bonds of bulk Ov.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, the photoacoustic (PA) technique can be applied to simultaneous measurements, regardless of sample transparency. The PA technique is a method for absorption spectroscopy that is applicable to even opaque and strongly scattering materials because it detects photoabsorption indirectly through photothermal waves generated by relaxation of the photoexcited states. , We have so far set up various in situ measurement systems, including PEC reaction over a photoelectrode and a particulate photocatalyst. , Here, we propose a simple method for thickness optimization by combination of the PA technique and step scanning of focused laser light. To accomplish it, a photoelectrode with a film-thickness gradient was prepared by electrophoretic deposition of tungsten­(VI) oxide (WO 3 ) particles while pulling up the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 We have so far set up various in situ measurement systems, including PEC reaction over a photoelectrode 14 and a particulate photocatalyst. 15,16 Here, we propose a simple method for thickness optimization by combination of the PA technique and step scanning of focused laser light. To accomplish it, a photoelectrode with a film-thickness gradient was prepared by electrophoretic deposition of tungsten(VI) oxide (WO 3 ) particles while pulling up the substrate.…”
Section: ■ Introductionmentioning
confidence: 99%